SPEECH ACTS ANALYSIS OF PRE-SERVICE TEACHERS AND STUDENTS AT SMK NEGERI 1 SINGARAJA - Putri, Kadek Dhea Paramitha Amara; Putra, I Nyoman Adi Jaya; Ramendra, Dewa Putu (Yavana Bhasha : Journal of English Language Education, 2021)
This research aims to analyze the kind of speech act used by pre-service teachers and students of SMK Negeri 1 Singaraja in WhatsApp as learning media. Investigate the most dominant speech act used by pre-service teachers and students, and analyze the kind of instructional function used by the pre-service teachers. The data were analyzed using descriptive qualitative. The subject of this research is the pre-service teacher and students in SMK Negeri 1 Singaraja. The data were collected through observation and interview. The data from the observation was collected using an observation sheet which developed from Searle’s (1969) theory of speech act and Johnson’s (1997) theory of instructional function. The interview has been done semi-structured using an interview guide. The result shows that the pre-service teacher use four speech act in the learning activity; representative, directive, commissive, and expressive. The pre-service teacher uses directive speech to act dominantly to make the students active in the learning process. Meanwhile, the students use four speech act, including representative, directive, commissive, and expressive. The students use representative in dominant to be active and getting feedback in the learning activity. The kinds of the instructional function used by the pre-service teacher are control, organize, and motivational. It was found that the directive speech act functioned as control. Commissive functioned as organize. And expressive as motivational function